Lucky Leap Day - Walker, Ann Marie (Sourcebooks Casablanca, 2022)
"A whirlwind trip to Ireland is supposed to end with a suitcase full of wool sweaters and souvenir pint glasses, not a husband you only just met! But after one too many whiskeys, fledgling screenwriter Cara Kennedy takes a page out of someone else's script when she gets caught up in the Irish tradition of women proposing on Leap Day. Waking the next morning with a hot guy in her bed and a tin foil ring on her finger was definitely not what she expected...and then the new life they forge in LA tests her to her limits.."--